The Relationship Between Prostate Volume Measured Transabdominal Ultrasound And International Prostate Symptom Score In Patients With Benign Prostate Hypertrophy - Ulum mahfud, Miftakhul; Nida Faradisa Fauziyah (Sean Institute, 2025)
Benign prostatic hypertrophy (BPH) refers to the enlargement of the prostate gland or urinary dysfunction due to prostate enlargement. Transabdominal ultrasonography is one method used to assess the prostate. The validated International Prostate Symptom Score (IPSS) questionnaire is the best way to evaluate the severity of lower urinary tract symptoms most often caused by BPH. This study is a diagnostic test research with a cross-sectional design. Sampling technique was consecutive sampling method on BPH patients recorded in the Radiology Department of Dr. Moewardi Regional General Hospital during the period from July to August 2023. The total sample consisted of 31 individuals. Research data were obtained through medical record data. Statistical analysis used normality analysis and Spearman correlation test. In this study, 31 patients were diagnosed with BPH. The mean age was 64.93 ± 11.18 years. The majority of patients had grade 1 volume category (67.7%), and most patients had moderate IPSS scores (51.6%). The Spearman correlation test results showed a strong significant relationship between prostate volume results via transabdominal ultrasound and IPSS scores in a positive direction. There is a significant relationship between prostate volume results via TAUS and IPSS scores. The higher the prostate volume value, the higher the IPSS score obtained.